1994
DOI: 10.1093/ajcn/59.4.810
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of childhood body mass index values for overweight at age 35 y

Abstract: Larger body mass index values (BMI in kg/m2) are associated with increased morbidity and mortality in adulthood and there are significant correlations between BMI values in childhood and in adulthood. The present study addresses the predictive value of childhood BMI for overweight at 35 +/- 5 y, defined as BMI > 28 for men and > 26 for women. Analyses of data for 555 white children indicated that overweight at 35 y can be predicted from BMI at younger ages. The prediction is excellent at age 18 y, good at 13 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
360
2
27

Year Published

2000
2000
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 662 publications
(405 citation statements)
references
References 28 publications
16
360
2
27
Order By: Relevance
“…For example, in the ZLS, 10% of 12 y-old girls had a BMI 20.7 and 3% had a BMI 22.4; in the present study, the corresponding percentages for 12 y-old girls were 33% and 26%. Although obesity may contribute to morbidity in childhood (for example, as a risk factor for childhood hypertension), its main importance as a public health problem is that it commonly tracks into adulthood (Rolland-Cachera et al, 1987;Guo et al, 1994;Must & Strauss, 1999). In the US, the risk of developing adult obesity (BMI 28) in children aged b 9 y who are obese approaches 80% at age 35 y (Guo & Chumlea, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the ZLS, 10% of 12 y-old girls had a BMI 20.7 and 3% had a BMI 22.4; in the present study, the corresponding percentages for 12 y-old girls were 33% and 26%. Although obesity may contribute to morbidity in childhood (for example, as a risk factor for childhood hypertension), its main importance as a public health problem is that it commonly tracks into adulthood (Rolland-Cachera et al, 1987;Guo et al, 1994;Must & Strauss, 1999). In the US, the risk of developing adult obesity (BMI 28) in children aged b 9 y who are obese approaches 80% at age 35 y (Guo & Chumlea, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of childhood obesity into adulthood has been shown by several studies (Rolland Cachera et al, 1987;Siervogel et al, 1991;Serdula et al, 1993). Guo et al (1994) have shown that overweight during childhood, especially beyond 8 years, is an important risk factor for overweight at the age of 35 years. Obesity in adolescents is not only associated with hypertension and abnormal lipid profile, but also shows clustering of risk factors for cardiovascular disease (Chu et al, 1998).…”
Section: Introductionmentioning
confidence: 93%
“…[4][5][6]14 Overweight is associated with many diseases, 1,[15][16][17] and the greater the degree of overweight as a child, the greater the likelihood that child will be overweight as an adult. 18,19 Extensive research addressing the intersection of TV use and child overweight has included known risk factors for child overweight, such as sociodemographics (e.g., gender, ethnicity, household income, parent education), 20,21 dietary intake (amounts and types of foods eaten), 13 presence of TV at meals, 12 perception of parental weight status 5,20 and measures of physical activity. 4,22 However, studies of TV use and child overweight have largely overlooked the presence of a TV in a child's bedroom.…”
Section: Introductionmentioning
confidence: 99%